The impact of brand use on innovation performance: Empirical results for Germany - Dirk Crass (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The market launch of product innovations is the most visible output of a firm's investment in innovation activities. To achieve this objective most efficiently, firms strengthen their technological capabilities, acquire external knowledge in a number of different ways, and optimize their innovation process. The success of a firm's innovation strategy has two dimensions: First, the ability of a firm to master the research and development process, leading to the market introduction of a product innovation. Second, the ability to turn the market introduction of a product innovation into commercial success. While a firms technological abilities make a product innovation possible, this product might face a lack of interest among potential customers after its market introduction. The introduction of a product innovation under a brand name might generate interest, adds credibility and reputation and has the potential for the firm to better appropriate the returns from its innovations. This paper investigates the role of brand use for the commercial success of product innovations, using a representative sample of German firms. The results show that firms can improve the odds of commercial success by pursuing a branding strategy. The market introduction of a product innovation is shown to be associated with 35% larger sales if the firm uses an established brand to introduce the product innovation into the market.
urn:nbn:de:bsz:180-madoc-374915
Keywords: O32; O34; 330; innovation performance; brands; trademarks; innovation; Germany